2017
DOI: 10.1002/ps.4645
|View full text |Cite
|
Sign up to set email alerts
|

European corn borer (Ostrinia nubilalis Hbn., Lepidoptera: Crambidae): comparing the performance of a new bisexual lure with that of synthetic sex pheromone in five countries

Abstract: The bisexual lure will provide growers with a new and efficient method for detection and monitoring of O. nubilalis. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 33 publications
0
11
0
2
Order By: Relevance
“…Recently, it has been found that the addition of 4-methoxy-2-phenethyl alcohol, also isolated from maize, to this compound increases the catchability of traps by a factor of 3-5 (Tóth et al, 2016). Tests conducted in five European countries of this semiochemical combination under the commercial name 'bisex lure' has confirmed this conclusion (Tóth et al, 2017). The results of our 2019 pilot tests of traps baited with 'bisex lure' also indicate that the combination of these semiochemicals is highly effective for monitoring ECB both in the Krasnodar Territory and Voronezh Region .…”
Section: Introductionmentioning
confidence: 79%
“…Recently, it has been found that the addition of 4-methoxy-2-phenethyl alcohol, also isolated from maize, to this compound increases the catchability of traps by a factor of 3-5 (Tóth et al, 2016). Tests conducted in five European countries of this semiochemical combination under the commercial name 'bisex lure' has confirmed this conclusion (Tóth et al, 2017). The results of our 2019 pilot tests of traps baited with 'bisex lure' also indicate that the combination of these semiochemicals is highly effective for monitoring ECB both in the Krasnodar Territory and Voronezh Region .…”
Section: Introductionmentioning
confidence: 79%
“…Таким образом, полученные в 2019 г. результаты подтверждают вывод [7] о перспективности семиохемиков для мониторинга кукурузного мотылька, особенно в северных очагах его вредоносности, где ловушки с половыми феромонами не обеспечивают надежного мониторинга вредителя. № 19-016-00128).…”
Section: а бunclassified
“…Исследования, выполненные в Институте защиты растений (Будапешт, Венгрия), выявили высокую аттрактивность двух летучих семиохемиков кукурузыфенилацетальдегида и 4-метокси-2-фенэтилового спирта для имаго вредителя [6], которая была подтверждена полевыми испытаниями, проведенными в ряде европейских стран [7].…”
unclassified
“…Since 2013 in the Hajdúság, 16 studies have been carried out during development of bisexual lure, targeting mainly the European corn borer (Ostrinia nubilalis) (Tóth et al 2016, the silver Y moth (Autographa gamma) ) and the cotton bollworm (Helicoverpa armigera) . Here, we discuss the non-target Lepidoptera catches of these field studies to provide a checklist of the Macroheterocera fauna and to draw attention to the need for further intensive investigations of the region.…”
Section: Introductionmentioning
confidence: 99%